Teacher's research motivation - Impact factors - Huỳnh, Nhật Nghĩa (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Scientific research is one of major responsibility to help lecturers improve professional knowledge for teaching and application to life, enriching knowledge treasures and developing society. However, in fact, in many universities, the scientific research activities of lecturers have not achieved the expected results. The content of the article focuses on studying the factors affecting the scientific research motivation of lecturers, through the method of reviewing documents from articles published in domestic and foreign scientific journals, then providing a research model as a basis for further research.